Practical Aspects of Design Science European Design Science Symposium, EDSS 2011, Leixlip, Ireland, October 14, 2011, Revised Selected Papers - Helfert, Markus; Donnellan, Brian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the European Design Science Symposium, EDSS 2011, held in Leixlip, Ireland, in October 2011 held in conjunction with the Intel European Research and Innovation Conference, ERIC 2011. The 15 revised full papers presented were carefully reviewed and selected from various submissions. The papers are organized in topical sections on design science and processes; evaluation and utility; and applying design science.
Design science and processes -- evaluation and utility -- applying design science.
Keywords: Computer science; Computer system performance; Software engineering; Computer aided design; Information Systems; Computer Science; Management of Computing and Information Systems; User Interfaces and Human Computer Interaction; Computer-Aided Engineering (CAD, CAE) and Design; System Performance and Evaluation; Software Engineering; Models and Principles